Comparative analysis of military medical personnel training in Russia and Europe in the 18–19th centuries - I. M. Chizh; I. V. Karpenko (Сеченовский вестник)
The article discusses the history of military medical training in Russia and Western Europe in XVIII–XIX centuries. The leading trend in military medical training in all compared countries was the introduction of militarymedical disciplines: military field surgery, military hygiene and sanitation tactics. It was not until the 19th century when this trend prevailed in all of the compared countries. Though this trend had much in common in all of the compared countries there were certain national peculiarities in military medical training at the time.